ABIFLOX EFFICACY IN COMPLEX THERAPY OF PATIENTS WITH COMMUNITY ACQUIRED PNEUMONIA - Lyadova, T. I.; VolobuyevaО. V.; SevastyanovaТ. V.; SavvoА. N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
The article presents the results of the study, during which the efficacy of levofloxacin in the treatment of patients with community-acquired pneumonia was evaluated. It was found that levofloxacin is a highly effective treatment for patients with community-acquired pneumonia.